2019
DOI: 10.1016/j.cub.2018.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Superior Colliculus GABAergic Neurons Are Essential for Acute Dark Induction of Wakefulness in Mice

Abstract: Graphical Abstract Highlights d GABAergic neurons in the SC receive direct input from RGCs d Acute dark induction of wakefulness requires SC GABAergic neurons d VTA dopaminergic neurons receive direct innervations from GABAergic neurons in the SC d VTA dopaminergic neurons are necessary for acute dark induction of wakefulness

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 40 publications
(51 reference statements)
3
57
1
Order By: Relevance
“…Neurons that did not satisfy these criteria were identified as TH− neurons ( Supplementary Fig. 5j), as previously described [12,25,56,57].…”
Section: In Vitro Electrophysiologymentioning
confidence: 99%
“…Neurons that did not satisfy these criteria were identified as TH− neurons ( Supplementary Fig. 5j), as previously described [12,25,56,57].…”
Section: In Vitro Electrophysiologymentioning
confidence: 99%
“…While the function of some SC neurons have been studied during behavior [23][24][25][26] ,characterization of GABAergic neurons in the intermediate and deep layers has primarily been limited to anatomy and slice physiology 33,34,38,49 . We have identified a functional role for these neurons in mediating spatial choice via intercollicular inhibition ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These and other data showing that SC activity reflects target value and other decision-related variables 12,21,22 demonstrate that the SC, traditionally appreciated for initiating orienting motor commands, is required for choosing where to move 7 . While the SC has recently served as an exquisite experimental system for probing neural circuit function in multiple behavioral contexts [23][24][25][26] , how SC circuits mediate spatial choice remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In nocturnal rodents, the SC has been shown to be critical for maintaining sleep when the lights are on (Miller et al, 1998). It has been recently shown that GABAergic neurons in the SC are critical for inducing wakefulness when the lights are off (Zhang et al, 2019). In addition, light input is critical for the SC to develop properly (Prichard et al, 2007).…”
Section: Discussionmentioning
confidence: 99%